PENGARUH DEWAN DIREKSI, DEWAN KOMISARIS, KOMISARIS INDEPENDEN, KOMITE AUDIT, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN - Aisyah Yuliyanti; Nur Cahyonowati (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of good corporate governance (GCG) on the financial performance of manufacturing companies. The variables used in this study are independent variables consisting of the board of directors, board of commissioners, independent commissioners, audit committee, managerial ownership, and institutional ownership, as well as the dependent variable in the form of financial performance proxied by Return On Assets (ROA).The study population is the entire manufacturing companies listed on the Indonesia Stock Exchange during 2018-2021. Using the purposive sampling technique, 146 enterprises were obtained as the sample. Hypothesis testing was conducted a multiple linear regression analysis with SPSS version 23 program help.The results of this study show that the board of directors, board of commissioners, managerial ownership, and institutional ownership have a negative and insignificant effect on financial performance. Independent commissioners have a positive and significant effect on financial performance. While the audit committee has a positive but insignificant effect on financial performance.